2008
DOI: 10.1063/1.2845019
|View full text |Cite
|
Sign up to set email alerts
|

Test Results from a Simulated High Voltage Lunar Power Transmission Line

Abstract: Abstract. The Alternator Test Unit (ATU) in the Lunar Power System Facility (LPSF) located at the NASA Glenn Research Center (GRC) in Cleveland, OH was modified to simulate high voltage transmission capability. The testbed simulated a 1 km transmission cable length from the ATU to the LPSF using resistors and inductors installed between the distribution transformers. Power factor correction circuitry was used to compensate for the reactance of the distribution system to improve the overall power factor. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A high-frequency AC system of 50kW with a high-voltage transmission line is simulated in [70] for lunar EPS. It is observed that the leakage inductance of the transformer is 10 times the transmission line, and the combined leakages of the two transformers are 60% of the alternator inductance.…”
Section: Power Distribution System For Space Mgsmentioning
confidence: 99%
“…A high-frequency AC system of 50kW with a high-voltage transmission line is simulated in [70] for lunar EPS. It is observed that the leakage inductance of the transformer is 10 times the transmission line, and the combined leakages of the two transformers are 60% of the alternator inductance.…”
Section: Power Distribution System For Space Mgsmentioning
confidence: 99%
“…The generated or stored power requires a suitable means for distribution to the consumption units using AC, DC or a hybrid AC-DC system. A 50kW lunar EPS with a high voltage and frequency is simulated by the authors of [47]. It has been observed that, although a higher frequency of the power system decreases the capacitor and power converter size, the skin effect and reactive inductance of the line increase, thereby minimally affecting the mass of the entire system [8].…”
Section: Power Distribution Technologiesmentioning
confidence: 99%